2018
DOI: 10.1590/0037-8682-0338-2016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal schistosomiasis: IL-2, IL-10 and regulatory T lymphocytes to unrelated antigen in adult offspring mice

Abstract: Separately, gestation or nursing induced immunosuppressive cells in infected mothers, but improved anti-OA immunity when combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Maternal infection by S. mansoni can alter the degree of immune competence of the offspring in the long term, either through in-utero contact or breastfeeding. (2,3,4,5) In this study, the effects of gestation and breastfeeding were evaluated separately in S. mansoni-infected mothers. Therefore, the expression of HDACs, and cytokine production by lymphocytes and macrophages was assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal infection by S. mansoni can alter the degree of immune competence of the offspring in the long term, either through in-utero contact or breastfeeding. (2,3,4,5) In this study, the effects of gestation and breastfeeding were evaluated separately in S. mansoni-infected mothers. Therefore, the expression of HDACs, and cytokine production by lymphocytes and macrophages was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In studies using immunisation with ovalbumin as adjuvant, gestation in infected mothers was correlated with increased production of IL-10. (2,5) Furthermore, Li et al (19) reported the positive regulation of HDAC9 in immature peritoneal macrophages through the action of acetyltransferase Dnmt3, leading to increased production of IFN-α and IFN-β via deacetylation of kinase TBK1. Mice deficient for Dnmt3a showed greater susceptibility to infection by vesicular stomatitis virus (VSV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation